An Unusual Presentation of a Large Calcified Thyroid Nodule - Umesh Jayarajah; Pradeep Wijerathne; Oshan Basnayake; Sanjeewa Seneviratne (Case Reports in Surgery)
This case highlights the rare occurrence of a large benign calcified nodule of the left lobe of the thyroid gland with associated obstructive symptoms. Unusually, the calcification was confluent with similar calcified nodules in the subcutaneous tissue plane. The symptoms were alleviated following a total thyroidectomy.